2021
DOI: 10.1177/03010066211052943
|View full text |Cite
|
Sign up to set email alerts
|

Semantically Congruent Bimodal Presentation with Divided-Modality Attention Accelerates Unisensory Working Memory Retrieval

Abstract: Although previous studies have shown that semantic multisensory integration can be differentially modulated by attention focus, it remains unclear whether attentionally mediated multisensory perceptual facilitation could impact further cognitive performance. Using a delayed matching-to-sample paradigm, the present study investigated the effect of semantically congruent bimodal presentation on subsequent unisensory working memory (WM) performance by manipulating attention focus. The results showed that unisenso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 56 publications
4
7
0
Order By: Relevance
“…In particular, English teaching in colleges and universities has been deeply integrated with multimedia teaching. Teachers basically use multimedia teaching mode in class [ 1 ]. However, although this teaching mode has made some progress with the traditional teaching mode, it still continues the drawbacks of the traditional teaching mode, especially the students' enthusiasm in the classroom and learning initiative.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, English teaching in colleges and universities has been deeply integrated with multimedia teaching. Teachers basically use multimedia teaching mode in class [ 1 ]. However, although this teaching mode has made some progress with the traditional teaching mode, it still continues the drawbacks of the traditional teaching mode, especially the students' enthusiasm in the classroom and learning initiative.…”
Section: Introductionmentioning
confidence: 99%
“…Working memory (WM) is typically considered a system with limited capacity that can process, store, and monitor information in a short period [1], which is the ability and/or resources to concurrently process and store task-relevant information or coordinate the processing of multiple competing inputs [2]. Some studies have reported that WM involves the temporal maintenance of an active representation of external perception information so that it is available for subsequent retrieval processing [3]. Recent evidence suggests that brains tend to aggregate and analyze information from different sources with connections to form a unified cognitive representation [4] and demonstrate a bimodal WM retrieval advantage [5].…”
Section: Introductionmentioning
confidence: 99%
“…The multisensory congruency relationship reflects the tendency to associate seemingly arbitrary features or stimulus dimensions that have a certain relationship under multisensory conditions [3,7]. Previous multisensory studies have indicated that multisensory integration efficiency was modulated by high-level semantic relationships between different sensory modalities [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations